Methods of Controlling Diseases and Pests of Grapevines - Usenbayev Almas Marsetbay Uli (American Journal of Biodiversity, 2026)
This article examines the main diseases and pests that damage the grapevine (Vitis vinifera L.) and provides an overview of effective control methods. Fungal diseases commonly found in vineyards, such as downy mildew (mildew), powdery mildew (oidium), and anthracnose, as well as sucking pests, severely affect the leaves, shoots, and fruits of the plant, leading to a significant decrease in yield and product quality. The importance of integrated management methods, including agrotechnical, biological, and chemical control measures, is analyzed. In addition, the preventive and therapeutic properties of preparations such as Bordeaux mixture, copper sulfate, iron sulfate, and lime-sulfur solution are highlighted.